Menyoal Wacana "Golput" dari Sisi Hukum Tata Negara - muntoha muntoha (Jurnal Hukum IUS QUIA IUSTUM, 2004)
Attitude and action of white passive voter is the right and it is valid iegaily, but the political process for the future is the determination of national leadership that it needs the active participation from public as the right of state. If the amount of passive voter group are reaching till over 50 %, it means that the white group has delegated the general election, even the meaning of white group have changed as manifestation of development of state.